FAKTOR PENYEBAB KESULITAN SISWA BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) DI SMPN 01 PADANG GELUGUR KABUPATEN PASAMAN - Ainun Mardiah; Alimir Alimir; Darul Ilmi; Jasmienti Jasmienti (KOLONI, 2022)
Learning to learn is defined as the difficulty of students in receiving or absorbing lessons at school. And the learning difficulties experienced by these students occur at the time of learning that is delivered or assigned by the teacher. So this writing is motivated by the problems found, including the lack of utilization of facilities to support PAI learning. This type of research is using qualitative descriptive research methods. To collect data, the writer did by observation, interview and documentation. After the data is collected, data processing and analysis is carried out. Furthermore, the technique of guaranteeing the validity is carried out by means of trigulation. Based on the results of the research obtained, it can be concluded that there are factors that cause learning difficulties because many students do not study MDA/TPQ so that they have difficulty memorizing, and there are still many students who study PAI so they have difficulty learning by studying well, and there are still many parents who do not unite or do not see how the association is outside their home so that students who are in school do not focus on learning because many of their children's friends are not in school, the next factor that causes difficulties for children to learn PAI is because there are still many students who do not intend because there are still many students who disturbing their friends who are studying, and there are still many students who are too fond of playing cellphones, so they forget to study, and when they are studied by the PAI teacher they can't answer because they don't study, then they don't learn to play a role in helping children learn because many people old only up to elementary school and less understand PAI learning. Keywords: Factors causing student learning difficulties, Islamic Religious Education.